2014
DOI: 10.1093/jac/dku273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gidB alterations responsible for streptomycin resistance in Mycobacterium tuberculosis

Abstract: We conclude that gidB mutations address many unanswered questions and explain the whole story behind phenotypic streptomycin-resistant strains exhibiting no mutation in rpsL or rrs. They also validate the hypothesis of sequential progression of resistance from low to high due to the existence of gidB alterations in the genetic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…The occurrence of gid B mutations in strains reduces drug pressure for selection of highly resistant isolates, therefore it has been suggested that high-level streptomycin resistant strains (e.g. rps L mutants) arise more frequently in gid B mutants than in wild-type cells [61]. We observed six streptomycin resistant strains without mutations in rps L, rrs or gid B.…”
Section: Discussionmentioning
confidence: 78%
“…The occurrence of gid B mutations in strains reduces drug pressure for selection of highly resistant isolates, therefore it has been suggested that high-level streptomycin resistant strains (e.g. rps L mutants) arise more frequently in gid B mutants than in wild-type cells [61]. We observed six streptomycin resistant strains without mutations in rps L, rrs or gid B.…”
Section: Discussionmentioning
confidence: 78%
“…In each case, the frameshift occurs within the region encoding the GidB methyltransferase domain. Mutations in gidB (rsmG) are associated with low-level streptomycin resistance in several species of bacteria including S. aureus [33][34][35][36] and it is speculated that loss of 16S methylation lowers the binding affinity of streptomycin thus conferring the resistance phenotype 35 . Here, a gidB transposon mutant was found to be 4-fold less susceptible to steptomycin ( Table 1, Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…The study by Spies et al showed gidB mutations in 49% of the streptomycin resistant clinical isolates studied and suggests efflux pump inhibitors could act in synergy with mutations in gidB to confer low-level streptomycin resistance in M. tuberculosis [86]. Other studies showed a similar percentage of gidB mutations associated with streptomycin resistant M. tuberculosis clinical isolates [55,56]. Also, the percentage of gidB mutations associated with streptomycin resistant M. tuberculosis clinical isolates from different regions of the world were seen in 34%, 3%, and 38% of streptomycin resistant M. tuberculosis clinical isolates in Pakistan, Cameroon, and Poland, respectively [82e84].…”
Section: Antibiotic Resistancementioning
confidence: 95%